Public Health and Politics: An Inextricable Connection - Mustafa Hussain Almotawah et al. (International Journal of Scientific Research and Innovative Studies, 2024)
Public health and politics are interdependent, influencing each other through the creation and implementation of policies, resource allocation, and decision-making at local, national, and global levels. Political decisions often determine public health priorities, funding, and accessibility, while public health issues can shape political agendas and actions. This paper explores the dynamic relationship between public health and politics, highlighting their shared challenges, opportunities, and implications for equitable healthcare delivery. Received Date: July 08, 2024 Accepted Date: July 29, 2024 Published Date: August 01, 2024 Available Online at: https://www.ijsrisjournal.com/index.php/ojsfiles/article/view/297 DOI: https://doi.org/10.5281/zenodo.14581656